2010
DOI: 10.1080/14763141.2010.495414
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical analysis of the penalty-corner drag-flick of elite male and female hockey players

Abstract: The aim of this study was to analyse the kinematic sequencing in the penalty-corner drag-flicks of elite male and female field hockey players of international calibre. Thirteen participants (one skilled male drag-flicker and six male and six female elite players) participated in the study. An optoelectronic motion analysis system was used to capture the drag-flicks with six cameras, sampling at 250 Hz. Select ground reaction force parameters were obtained from a force platform which registered the last support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
8
14

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 9 publications
4
15
8
14
Order By: Relevance
“…This method may be useful in the training process, especially in re gards to maintaining correct load optimization as well as to an athlete's physiological welfare during competition [57]. Similar results can also be attained by analyzing selected camera recordings, including important parts of game play, such as penalty corners [58].…”
Section: Tacticssupporting
confidence: 55%
“…This method may be useful in the training process, especially in re gards to maintaining correct load optimization as well as to an athlete's physiological welfare during competition [57]. Similar results can also be attained by analyzing selected camera recordings, including important parts of game play, such as penalty corners [58].…”
Section: Tacticssupporting
confidence: 55%
“…It may be that the shorter distance to goal and the lighter ball allows athletes to propel a more powerful and effective shot than can be achieved outdoors. López de Subijana et al (2010) reported elite female athletes to generate a substantially slower ball speed than their male counterparts. The applicability of these findings to the outdoor scenario and the male game requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike the hit, there is no limitation regarding the maximum ball height when the first shot to score a goal from a penalty corner is a drag-flick. Thus, with a hard plastic ball travelling at velocities in excess of 43 mph,4 the drag-flick presents a serious injury threat to defending players (in particular) who are positioned behind the goal line in an attempt to block such shots.…”
Section: Contextualising the Problemmentioning
confidence: 99%